The National Council of Justice and its limits on the activities of extrajudicial offices (Revista do Tribunal Regional Federal da 3ª Região, 2020)
The present article will approach the so called CNJ, created by the 45/2004 amendment and displayed on article 103-B of our Constitution, and its relation and limits with notaries and their extra judicial offices, that are defined on article 236 of the Constitution, being managed by delegation of Public authorities.
Keywords: CNJ; extrajudicial offices; limits; regulation